Activation of platelet protein kinase C by ultraviolet light B mediates platelet transfusion–related acute lung injury in a two‐event animal model. Issue 4 (31st July 2012) - Zhi, Li; Chi, Xuan; Gelderman, Monique P.; Vostal, Jaroslav G.
<x xml:space="preserve">Abstract</x> BACKGROUND: We recently reported that infusion of ultraviolet light B (UVB)‐exposed human platelets (HPs) can be the second event that mediates acute lung injury (ALI) in a two‐event mouse model of transfusion‐related acute lung injury (mTRALI). We have now identified changes in HPs induced by UVB light and responses of the recipient animal that mediate the mTRALI. STUDY DESIGN AND METHODS: Effects of UVB on HPs were monitored by flow cytometry and aggregation. HPs exposed to UVB, with or without inhibitors to specific biochemical pathways, were infused into lipopolysaccharide (LPS)‐primed severe combined immunodeficient (SCID) mice. ALI was monitored by protein elevations in bronchoalveolar lavage fluid (BALF). RESULTS: UVB increased fibrinogen binding and potentiated HP aggregation. Infusion of UVB HPs into LPS‐primed SCID mice led to macrophage inflammatory protein 2 (MIP‐2) elevations in plasma and BALF and resulted in ALI. Protein kinase C (PKC) inhibitors prevented UVB‐induced HP changes in vitro and reduced MIP‐2 elevation and mTRALI in vivo. Blocking of fibrinogen binding to HP αIIbβ3 with c7E3 monoclonal antibody prevented mTRALI. MIP‐2 elevation in vivo in response to UVB HPs was essential for ALI since blocking of MIP‐2 receptor in vivo prevented mTRALI. CONCLUSION: PKC signaling mediates UVB‐induced HP fibrinogen binding and aggregation in vitro. The host animal responds to an infusion of UVB HPs by MIP‐2 elevation that mediates downstream mTRALI. Elucidation of molecular mechanisms in UVB HP–mediated mTRALI may provide insight into pulmonary adverse events reported with UV‐irradiated pathogen‐reduced platelets.